Distinct regulations driving YAP1 expression loss in poroma, porocarcinoma and RB1‐deficient skin carcinoma. Issue 6 (22nd February 2023) - Kervarrec, Thibault; Frouin, Eric; Collin, Christine; Tallet, Anne; Tallegas, Matthias; Pissaloux, Daniel; Tirode, Franck; Guyétant, Serge; Samimi, Mahtab; Gaboriaud, Pauline; Touzé, Antoine; Schrama, David; et al.
Abstract : Aims: Recently, YAP1 fusion genes have been demonstrated in eccrine poroma and porocarcinoma, and the diagnostic use of YAP1 immunohistochemistry has been highlighted in this setting. In other organs,  loss of YAP1 expression can reflect YAP1 rearrangement or transcriptional repression, notably through RB1 inactivation. In this context, our objective was to re‐evaluate the performance of YAP1 immunohistochemistry for the diagnosis of poroma and porocarcinoma. Methods and results: The expression of the C‐terminal part of the YAP1 protein was evaluated by immunohistochemistry in 543 cutaneous epithelial tumours, including 27 poromas, 14 porocarcinomas and 502 other cutaneous tumours. Tumours that showed a lack of expression of YAP1 were further investigated for Rb by immunohistochemistry and for fusion transcripts by real‐time PCR ( YAP1 :: MAML2 and YAP1 :: NUTM1 ). The absence of YAP1 expression was observed in 24 cases of poroma (89%), 10 porocarcinoma (72%), 162 Merkel cell carcinoma (98%), 14 squamous cell carcinoma (SCC) (15%), one trichoblastoma and one sebaceoma. Fusions of YAP1 were detected in only 16 cases of poroma ( n  = 66%), 10 porocarcinoma (71%) all lacking YAP1 expression, and in one sebaceoma. The loss of Rb expression was detected in all cases except one of YAP1‐deficient SCC ( n  = 14), such tumours showing significant morphological overlap with porocarcinoma. In‐vitro experiments in HaCat cells showed that RB1 knockdown resulted in repression of YAP1 protein expression. Conclusion: In addition to gene fusion, we report that transcriptional repression of YAP1 can be observed in skin tumours with RB1 inactivation, including MCC and a subset of SCC. Abstract : Recently, YAP1 fusion genes have been demonstrated in eccrine poroma and porocarcinoma, resulting in YAP1 expression loss detectable by immunohistochemistry. In the present study, in addition to gene fusion mechanisms, we report that transcriptional repression of YAP1 can be observed in skin tumours with RB1 inactivation, including the majority of MCC and a subset of SCC, a morphological mimicker of porocarcinoma.